Edukasi dan Pelepasan Penyu untuk Konservasi Ekosistem Pesisir Pantai Nipah Berkelanjutan - Baiq Handayani Rinuastuti; Siti Nurmayanti; Mohammad Najib Roodhi; Abdurrahman; Tifani Dame Hasany; Isra Dewi Kuntari Ibrahim; Zefanya Andryan Girsang; Nurul Faradila (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
The community-based conservation program at Nipah Beach, North Lombok, was implemented to address significant threats to sea turtles, including illegal hunting, habitat destruction, marine pollution, and poorly managed tourism. The program involved collaboration between universities, the Turtle Conservation Community (TCC) Nipah, and local stakeholders. Key activities included public education, hatchling release, beach clean-ups, and eco-tourism development, conducted systematically through preparation, implementation, and evaluation stages. The program successfully released 1,752 hatchlings, reduced marine plastic waste by 40%, and increased community awareness of conservation by 27%. Despite challenges such as limited public understanding (43%) and restricted tourism capacity, the program achieved notable ecological, social, and economic benefits. Future potential lies in developing educational tourism packages and innovative waste management strategies, demonstrating the importance of integrating conservation, education, and community empowerment for sustainable biodiversity protection.